2018
DOI: 10.3390/app8091498
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Lactobacillus Plantarum CQPC10 on Activated Carbon Induced Constipation in Institute of Cancer Research (ICR) Mice

Abstract: Chinese Paocai is a traditional fermented food containing an abundance of beneficial microorganisms. In this study, the microorganisms in Szechwan Paocai were isolated and identified, and a strain of lactic acid bacteria (Lactobacillus plantarum CQPC10, LP-CQPC10) was found to exert an inhibitory effect on constipation. Microorganisms were isolated and identified via 16S rDNA. Activated carbon was used to induce constipation in a mouse model and the inhibitory effect of LP-CQPC10 on this induced constipation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Through this study, it was observed that the bacterium has a good inhibitory effect on constipation in the laboratory, which proves that it is a probiotic microorganism. The results of this study are similar to those of previous studies [6,11,13,23], which suggest that Lactobacillus can inhibit constipation and be used as intestinal microorganisms. At the same time, the results of molecular biology further show that CQPC05 can regulate constipation by regulating the intensity of gene expression in the small intestine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Through this study, it was observed that the bacterium has a good inhibitory effect on constipation in the laboratory, which proves that it is a probiotic microorganism. The results of this study are similar to those of previous studies [6,11,13,23], which suggest that Lactobacillus can inhibit constipation and be used as intestinal microorganisms. At the same time, the results of molecular biology further show that CQPC05 can regulate constipation by regulating the intensity of gene expression in the small intestine.…”
Section: Discussionsupporting
confidence: 90%
“…It has been proven that Lactobacillus possesses several functions. For example, Lactobacillus LF31 and Lactobacillus coryniformis have antioxidant effects [10], and Lactobacillus plantarum YS4 can prevent constipation in mice [11]. Our team investigated Szechwan-style pickled vegetables, and isolated and identified the microorganisms that they contain.…”
Section: Introductionmentioning
confidence: 99%
“…However, under stress conditions, heme, hydrogen peroxide (H 2 O 2 ), endotoxin, heavy metals, UV radiation, and hyperoxia/ hypoxia can initiate HO-1 expression through Nrf2 and show strong antioxidant activity through scavenging free radicals such as hydrogen peroxide. The Nrf2/HO-1 pathway is widely involved in the protection of tissues and organs, including heart, brain, liver, kidney, and nervous system, from oxidative stress-induced damage, making it one of the most important endogenous protection systems in the body (Zhang et al, 2018). Studies have found that anthocyanin upregulates HO-1 through serine/threonine protein kinase (Akt) and extracellular regulation of protein kinase (ERK1/2)/Nrf2 signaling pathways to eliminate ROS, thereby exerting a protective effect on hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…After closure, the PVDF membrane was cleaned by 1 × TBST, and the first antibody was incubated at 25°C for 2 hr; the second antibody was incubated at 25°C after 5 times of cleaning by 1 × TBST. Finally, Supersignal West Pico PLUS (Thermo Fisher Science) was used to spray PVDF film and placed in iBright FL1000 (Thermo Fisher Science) for observation (Zhang et al, ).…”
Section: Methodsmentioning
confidence: 99%